Simple Borax Qualitative Test in Benangkah Village, Bangkalan Regency - Fitroh Annisaul Mubarokah; Zulfa Noraini; Robiatul Adawiyah; Teguh Setiawan Wibowo (PT FORMOSA CENDEKIA GLOBAL, 2023)
Indonesia has a low level of awareness of health and food safety. This is proven by the fact that there are still many foods in circulation that contain harmful preservatives such as borax. Borax is a food additive used to increase food shelf life, shape, taste, and texture. The purpose of this community service is to educate the people in Benangkah village regarding the dangers of borax and how to identify it using simple tools and materials. The method used is the lecture method and demonstration simulation. The results of the community service showed that several food samples positively contained borax which was indicated by a change in color to brownish red after being dripped with turmeric solution.